2011
DOI: 10.1016/j.jfms.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of persistent viraemia and latent feline leukaemia virus infection in cats with lymphoma

Abstract: In the past, feline leukaemia virus (FeLV) infection, and also latent FeLV infection, were commonly associated with lymphoma and leukaemia. In this study, the prevalence of FeLV provirus in tumour tissue and bone marrow in FeLV antigen-negative cats with these tumours was assessed. Seventy-seven diseased cats were surveyed (61 antigen-negative, 16 antigen-positive). Blood, bone marrow, and tumour samples were investigated by two polymerase chain reaction (PCR) assays detecting deoxyribonucleic acid (DNA) seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
5

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 30 publications
3
37
0
5
Order By: Relevance
“…Whereas 59% of all cats with lymphoma or leukemia were FeLV antigen-positive in one German study from 1980 to 1995, only 20% of the cats were FeLV antigen-positive in the years 1996 to 1999 in the same university veterinary clinic (Hartmann et al, 1998). A recent study in this area confirmed the low prevalence of FeLV antigenemia in cats with lymphoma; in the study, 16 of 77 cats (21%) were FeLV antigen-positive (Stützer et al, 2011). In a study in the Netherlands, only four of 71 cats with lymphoma were FeLV-positive, although 22 of these cats had mediastinal lymphoma, which was previously highly associated with FeLV infection (Teske et al, 2002).…”
Section: Feline Leukemia Virus Infectionmentioning
confidence: 63%
“…Whereas 59% of all cats with lymphoma or leukemia were FeLV antigen-positive in one German study from 1980 to 1995, only 20% of the cats were FeLV antigen-positive in the years 1996 to 1999 in the same university veterinary clinic (Hartmann et al, 1998). A recent study in this area confirmed the low prevalence of FeLV antigenemia in cats with lymphoma; in the study, 16 of 77 cats (21%) were FeLV antigen-positive (Stützer et al, 2011). In a study in the Netherlands, only four of 71 cats with lymphoma were FeLV-positive, although 22 of these cats had mediastinal lymphoma, which was previously highly associated with FeLV infection (Teske et al, 2002).…”
Section: Feline Leukemia Virus Infectionmentioning
confidence: 63%
“…A low percentage of cats tested positive for feline retroviruses. None of feline skin lymphomas in other reports was associated with progressive FeLV infection, which implies a negligible role of FeLV in subcutaneous lymphomagenesis, and most likely reflects the decreasing prevalence of FeLV among cats in most countries and among cats with lymphomas in particular …”
Section: Discussionmentioning
confidence: 76%
“…Prevalence of progressive FeLV infection decreased in the general cat population due to routine screening of cats, separation of progressively infected cats and preventative FeLV vaccination programs since the 1990s. Consequently the number of FeLV‐associated lymphomas declined as well …”
Section: Introductionmentioning
confidence: 99%
“…Proviral DNA was detected in formalin-fixed, paraffin-embedded tumor tissue in 7/11 FeLV-negative cats with lymphoma [43]. However, other groups found evidence of provirus in only 1/22 [45] and in 0/50 FeLV antigen-negative lymphomas [47]. …”
Section: Clinical Signsmentioning
confidence: 99%